Evaluation of the Multiaxial Fatigue Life of Electro-Mechanical Actuator for Aircraft Blade Pitch Control Based on Certification Standards - Young-Cheol Kim; Dong-Hyeop Kim; Sang-Woo Kim (Aerospace, 2024)
To achieve the commercialization of electric vertical takeoff and landing (eVTOL) aircrafts, which have recently garnered attention as the next-generation means of transportation, objective certification based on rigorous procedures is essential. With the advancement of structural analysis technology, aircraft airworthiness standards recommend a combination of testing and analytical methods to demonstrate structural integrity. In this study, we propose analytical techniques for demonstrating the structural integrity of components for eVTOL aircrafts in accordance with airworthiness standards. We evaluated the static structural integrity and fatigue safety of an electro-mechanical actuator. Multibody dynamics analysis was performed to calculate the loads for application in finite element analysis. Subsequently, static analysis and fatigue analysis based on finite element analysis were conducted to calculate the safety margin and fatigue life of all key components. Therefore, we have confirmed the feasibility of utilizing analytical methods for the structural integrity assessment of aircraft components. We propose the utilization of the technique introduced in this study as one of the approaches for demonstrating compliance with airworthiness standards for eVTOL aircrafts through the application of analytical methods.